Time course of cognitive dysfunction and biochemical marker of CNS lesions S100ß in coronary artery bypass graft - E. V. Lebedeva; A. S. Gorokhov; E. D. Schastnyy; A. N. Repin; G. G. Simutkin; E. V. Shishneva; V. A. Perchatkin; A. K. Surovtseva; S. Winter; R. S. Karpov; N. A. Bokhan (Бюллетень сибирской медицины)
Objective: to study cognitive functions and level of proteins of acute brain damage in a group of patients receiving Cerebrolysin, and in a comparison group in the pre- and postoperative period of coronary artery bypass graft surgery.Materials and methods. The open-label randomized comparative controlled parallel study included 60 men. The average age in the group of patients receiving the therapy with Cerebrolysin was 61.5 (57÷66) years, and was – 61 (56÷65) years (р > 0.05) in the comparison group.Results. Groups differed statistically significantly according to the left ventricular ejection fraction: 56 (48÷64) – in the group of comparison, 61 (59÷65) – in the group of patients receiving therapy with Cerebrolysin (p < 0.05). In the group of patients receiving Cerebrolysin, an increase in score according to MMSE (р < 0.01) was noted from 25 (24÷27) to 26.2 (24–28) points, and in the group without brain neuroprotection in the preoperative period a decrease in score according the Mini-Mental State Examination was revealed to be from 25.5 (25÷27) to 25 (23÷27) (р < 0.01). Clinical value of the level of protein S100ß as a biological indicator of postoperative cognitive dysfunction after cardiac surgery was ambiguous and required additional research.Conclusion. Brain neuroprotection with use of Cerebrolysin (authors’ schema) promoted not only maintenance but also improvement of cognitive functions and decreased the likelihood of complications in mental activity after coronary artery bypass graft surgery under conditions of artificial circulation and cold cardioplegia, particularly in patients with a high risk for their development.